Cross-country differences in the effect of political connections on stock price informativeness. Issue 2 (August 2020) - Kusnadi, Yuanto; Srinidhi, Bin
Highlights: Political connections are negatively associated with stock price informativeness in an international sample. The negative relationship is only significant for firms in countries with low institutional quality. The negative relationship is driven by the connectedness of the owners. Abstract: Using an international sample of firms from 28 countries, we document that there exists a negative relationship between political connections and the informativeness of stock price, as measured by idiosyncratic volatility (IV). This finding is robust to alternative regression specifications, sub-samples analyses, and concerns related to endogeneity. A more detailed analysis shows that out of the different types of possible connections, the connectedness of the owners is the primary driver of this result. Further, the negative association is only significant for firms in countries characterized by low institutional quality (corrupted countries, countries with low access to external equity markets, and countries with low media penetration). There is no evidence of any relation between political connections and stock price informativeness for firms in countries characterized by high institutional quality. Overall, our results show that although political connections exacerbate rent-seeking that weaken the firms' information environment on average, the negative information consequences are compensated by the countries' institutional quality.